1975
DOI: 10.1007/bf00428900
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of behaviorally augmented tolerance to ethanol, and its relation to physical dependence

Abstract: Adult rats, required to perform a motor coordination task while under the influence of ethanol (2.2 g/kg) daily for 12 days, developed significant tolerance to the effects of ethanol, not only on this test but also on a food-motivated maze task. At the same time, they showed reduced shock threshold for production of a startle response, and reduced open field test scores 23 hrs after the last dose of ethanol. Other animals receiving the same dose of ethanol immediately after each training session on the coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…In the last three decades, several studies have suggested that learning factors contribute to the acquisition of ethanol tolerance, thus changing its classical concept (Chen 1968;Leblanc et al 1975;Holloway and King 1989;Kalant 1998;Larson and Siegel 1998). Recent studies have shown that the nucleus accumbens is involved in learning processes (Di Ciano et al 2001;Giertler et al 2003;Phillips et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the last three decades, several studies have suggested that learning factors contribute to the acquisition of ethanol tolerance, thus changing its classical concept (Chen 1968;Leblanc et al 1975;Holloway and King 1989;Kalant 1998;Larson and Siegel 1998). Recent studies have shown that the nucleus accumbens is involved in learning processes (Di Ciano et al 2001;Giertler et al 2003;Phillips et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This type of phenomenon has been variously referred to as behaviorally augmented tolerance, hehaviomlly contingent tolerance, or simply contingent tolerance. LeBlanc et al (1973LeBlanc et al ( ,1975 substantially accelerated the rate of development of tolerance to motor impairment by alcohol by placing motoric demands on rats exposed to alcohol. In an insightful analysis, Kalant, LeBlanc, and Gibbins (1971) proposed that the functional disturbance experienced in the drug state stimulates the development of tolerance.…”
Section: Historical Overviewmentioning
confidence: 99%
“…For example, rats acquire more tolerance to the disruptive effects of ethanol on well-learned operant performance when they are allowed to practice the task while intoxicated relative to animals receiving similar doses of ethanol following training (e.g., Chen 1968Chen , 1972LeBlanc et al 1973LeBlanc et al , 1975. This "intoxicated practice effect" has been attributed to the animal's acquisition of a task-specific compensation for the disruptive effects of alcohol on performance (Chen 1972;Wenger et al 1980Wenger et al , 1981.…”
mentioning
confidence: 99%